2001
DOI: 10.1148/radiology.218.3.r01mr39763
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascular Hepatocellular Carcinoma: Detection with Double Arterial Phase Multi-Detector Row Helical CT

Abstract: Double arterial phase imaging is recommended to improve detection of hypervascular HCCs and reduce false-positive lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
156
2
8

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(171 citation statements)
references
References 14 publications
5
156
2
8
Order By: Relevance
“…Histopathological studies have demonstrated a progressive increase in the arterial supply to nodules evolving toward malignancy, [28][29][30] providing the clues for the clinical diagnosis with imaging techniques. 20,[31][32][33][34][35] To give a solid basis for the noninvasive diagnosis, the EASL panel of experts determined that this pattern must be confirmed by two different imaging techniques in nodules larger than 2 cm. No reference was made to vascularity for nodules between 1 and 2 cm, and it was pointed out that these lesions require histopathological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies have demonstrated a progressive increase in the arterial supply to nodules evolving toward malignancy, [28][29][30] providing the clues for the clinical diagnosis with imaging techniques. 20,[31][32][33][34][35] To give a solid basis for the noninvasive diagnosis, the EASL panel of experts determined that this pattern must be confirmed by two different imaging techniques in nodules larger than 2 cm. No reference was made to vascularity for nodules between 1 and 2 cm, and it was pointed out that these lesions require histopathological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 We have examined the expression of ANG2 RNA in CRC metastases in the liver and compared the results with those observed in primary CRC tissue samples using the reverse-transcription polymerase chain reaction (RT-PCR) assay. Using laser capture microdissection (LCM), RNA content data on ANG2, ANG1, TIE2, and the VEGF gene, which encodes the putative angiogenic factor VEGF (vascular endothelial growth factor), were obtained for normal liver cells and for metastatic CRC cells in the liver, with reference to vessel density in each region of the liver.…”
mentioning
confidence: 99%
“…Therefore, fixed scanning time delay may have deteriorated the quality of dynamic imaging in some patients. It is likely that the use of bolus tracking or test bolus techniques (10,21) may improve the detection of hypervascular lesions using ferucarbotran-enhanced MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The scanning parameters were 1.25 mm ϫ 8 or 2 mm ϫ 4 detector configuration, 0.875-1.375 pitch, 5-mm slice thickness, 5-mm reconstruction interval, 120 kVp, and 300 -400 mA tube current. The scanning time delay for early arterial phase and late arterial phase imaging was determined by using a test bolus technique (10) or an automatic bolus tracking technique (11). The time from the contrast material injection until the initiation of the early arterial phase scan was 18 -36 seconds.…”
Section: Ct Imagingmentioning
confidence: 99%